2022
DOI: 10.3390/gels8110746
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and Ex Vivo Evaluation of Fluocinolone Acetonide–Acitretin-Coloaded Nanostructured Lipid Carriers for Topical Treatment of Psoriasis

Abstract: Psoriasis is chronic autoimmune disease that affects 2–5% of the global population. Fluocinolone acetonide (FLU) and acitretin (ACT) are widely used antipsoriatic drugs that belong to BCS classes II and IV, respectively. FLU exhibits side effects, such as skin irritation and a burning sensation. ACT also shows adverse effects, such as gingivitis, teratogenic effects and xerophthalmia. In the present study, topical nanostructured lipid carriers (NLCs) were fabricated to reduce the side effects and enhance the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…The ex vivo penetration study demonstrated lower permeation for the NLC gel co-formulated with fluocinolone acetonide and acitretin in comparison to the conventional fluocinolone acetonide and acitretin-containing gel. On the other hand, the skin deposition for the NLC formulation was greater than that of the conventional gel, verifying that NLCs were present in the deeper skin layers [ 112 ]. Table 4 summarizes the above-mentioned NLCs and their characteristics.…”
Section: Current Nanotechnology-based Approaches For the Topical Trea...mentioning
confidence: 99%
“…The ex vivo penetration study demonstrated lower permeation for the NLC gel co-formulated with fluocinolone acetonide and acitretin in comparison to the conventional fluocinolone acetonide and acitretin-containing gel. On the other hand, the skin deposition for the NLC formulation was greater than that of the conventional gel, verifying that NLCs were present in the deeper skin layers [ 112 ]. Table 4 summarizes the above-mentioned NLCs and their characteristics.…”
Section: Current Nanotechnology-based Approaches For the Topical Trea...mentioning
confidence: 99%
“…Although there are several conventional topical products with FA on the market, physical difficulties in applying the treatment, lack of visible effect, and, most importantly, numerous side effects lead to poor patient adherence and limit their efficacy. As a result, intensive research has concentrated on the design of nanotechnology-based drug delivery systems to ensure targeted delivery to the skin and enhance the benefit-risk ratio of topical corticosteroids such as FA (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%